BIENESTAR SOCIOEMOCIONAL DE LOS DOCENTES ECUATORIANOS EN TIEMPOS DE COVID-19 - López-Orellana, Cindy Tatiana; Piedra-Martínez, Elisa; Varela-Torres, Jorge Javier; Freire-Pesántez, Andrea; Baculima-Bacuilima, Janneth Lucía; Cordero-Cobos, Lucía (Universidad-Verdad, 2022)
El objetivo de este estudio fue identifcar el bienestar emocional de los docentes ecuatorianos durante la pandemia de la COVID-19, considerando las variables de género y edad. Participaron 313 docentes de preescolar, primaria y secundaria, a quienes se les aplicó una encuesta online sobre el bienestar docente, afectos positivos y negativos, apoyo social, desgaste emocional, ciberacoso y aspectos sobre la percepción de la situación personal en la pandemia. Los resultados informan que los docentes, en general, presentan un bienestar emocional positivo y una alta manifestación de afectos positivos; sin embargo, reportan un incremento en su carga laboral y doméstica. En relación con la edad, los docentes de menos de 40 años han percibido menor bienestar. Otra variable relevante fue el género, en donde las mujeres, presentaron un menor nivel de bienestar, mayor desgaste psíquico y menos afectos positivos. El modelo de regresión múltiple evidenció que las variables que más infuyen en el bienestar de los docentes son el desgaste emocional y los afectos positivos. En conclusión, estos resultados muestran las experiencias socioemocionales de los docentes durante la pandemia y permiten refexionar sobre acciones que se deberán seguir con el fn de favorecer su salud mental, elemento clave en la calidad educativa.. Palabras clave Afectos, bienestar emocional, desgaste, docentes, pandemia. Abstract This study aims to identify the emotional wellbeing of Ecuadorian teachers during the COVID-19 pandemic, and to analyze diferences by gender and age. A total of 313, elementary, middle and high school teachers participated by answering an online questionnaire about teacher well-bein, positive and negative afects, social support, emotional exhaustion, cyberbullying and aspects about the perception of the personal situation during the pandemic. The results of the study show that, teachers in general, present a positive emotional well-being and a high manifestation of positive afections; however, they report an increase in their work and domestic burden. In relation to age, teachers under the age of 40 have perceived less well-being. Another relevant variable was gender, where women presented a lower level of well-bein, positive and negative afects, social support, emotional exhaustion, cyberbullying and aspects about the perception of the personal situation during the pandemic. The results of the study show that, teachers in general, present a positive emotional well-being and a high manifestation of positive afections; however, they report an increase in their work and domestic burden. In relation to age, teachers under the age of 40 have perceived less well-being. Another relevant variable was gender, where women presented a lower level of well being, greater mental exhaustion and fewer positive afects. The multiple regression model showed that the variables that most infuence the wellbeing of teachers are emotional exhaustion and positive afects. In conclusion, these results show the socio-emotional experiences of teachers during the pandemic and allow us to refect on actions to follow in order to promote their mental health, a key ement in educational quality. Keywords Afections, burnout, emotional well-being, pandemic, teachers.